1989
DOI: 10.2165/00003088-198917040-00006
|View full text |Cite
|
Sign up to set email alerts
|

Release of Gentamicin from Acrylic Bone Cement

Abstract: The pharmacokinetics of gentamicin were studied after total hip joint arthroplasties performed with "Palacos R plus gentamicin' in 10 patients. Urine was collected at 12-hour intervals for 15 days after operation, and drainage fluids for 48, 72 or 108 hours. Blood samples were taken 3 and/or 5 hours after prosthesis implantation. High concentrations of gentamicin were found in drainage fluids. Excretion curves in drainage fluids or urine were fitted by a computer-aided design program (SIAM) and the mean curves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
35
0
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 13 publications
3
35
0
4
Order By: Relevance
“…Our data showing a local tissue concentration of antibiotics in excess of the MIC, even after 6 weeks of implantation, are consistent with data from the few studies analyzing antibiotic levels around the spacer in vitro or aspirates after several weeks [4,21,32]. Moreover the low rate of recurrence of infection with a two-stage approach supports the conclusion that the spacer releases sufficient, high amounts of antibiotics after that interval to treat infection and is not just fulfilling a physical, jointmaintaining function [9,10,25].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our data showing a local tissue concentration of antibiotics in excess of the MIC, even after 6 weeks of implantation, are consistent with data from the few studies analyzing antibiotic levels around the spacer in vitro or aspirates after several weeks [4,21,32]. Moreover the low rate of recurrence of infection with a two-stage approach supports the conclusion that the spacer releases sufficient, high amounts of antibiotics after that interval to treat infection and is not just fulfilling a physical, jointmaintaining function [9,10,25].…”
Section: Discussionsupporting
confidence: 91%
“…The question, whether a sufficient concentration of antibiotic in vivo is ensured for the entire spacer period, could not be answered satisfactorily in previous studies with spacers and the usual antibiotics. Previous in vivo studies of the release of antibiotics from bone cement have showed that only a minor portion (5%-18%) of gentamicin incorporated in bone cement is eluted [4,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is unlike the situation in Europe, where a variety of different antibioticloaded bone cements are commercially available. In vitro and in vivo studies have shown that only small amounts of the antibiotics incorporated in bone cement are actually released (Schurman et al 1978, Hoff et al 1981, Törholm et al 1983, Bunetel et al 1989, Chohfi et al 1998, because the release is largely a surface phenomenon. Antibiotics elute rapidly from the outer 50-100 µm of bone cement.…”
mentioning
confidence: 99%
“…However, the preliminary results of several pilot studies formed the basis for the estimation of the study sample. (Wahlig and Dingeldein 1980, Wahlig et al 1984, Salvati et al 1986, Bunetel et al 1989, Lindberg et al 1991) and 9-43 mg/ L of tobramycin (Soto-Hall et al 1983, Brien et al 1993, Masri et al 1998, Della Valle et al 2001). To our knowledge, the netilmicin peak values in drainage fluid recorded in our study have been the highest recorded to date.…”
Section: Discussionmentioning
confidence: 99%